ANALISIS FAKTOR PENYEBAB DAN STRATEGI PENCEGAHAN PEMBALAKAN LIAR (ILLEGAL LOGGING) DI KABUPATEN TABALONG - Kurniawan Basuki; Athailllah Mursyid; Ahmad Kurnain; Suyanto Suyanto (Universitas Lambung Mangkurat, 2013)
Tabalong Regency with an area of 3.946 km2, has a forest area of 2,087 km2; featuring lively activity going on illegal logging. The impact of environmental losses arising from the practice of illegal logging currently has been very well perceived by the people who live inside and outside of the Tabalong Regency. A variety of protective measures and safeguards the forest against illegal logging practices have been implemented, but not yet a lot of fruition. This is because the efforts that have been made less touched on the main problems of illegal logging practices, so I need to know the primary cause factor of occurrence of illegal logging practices in order to be compiled a concrete action and policy formulation that is strategic in preventing illegal logging practices. This study aims to explore the main factors that led to the practice of illegal logging in Tabalong Regency, as well as how prevention strategies. This research uses qualitative research methods with approach case studies, using interview techniques, observation and study of the literature. The results showed that the main factor is the cause of rampant illegal logging practices in Tabalong Regency is not effectively monitoring and control the administering of wood in preventing the occurrence of illegal logging practices. This is the cause of the occurrence a mode of “bleaching” against the wood results in illegal logging. Strategy of prevention of illegal logging in Tabalong Regency will need to be directed at efforts to increase the effectiveness of oversight and control over the administering of wood in preventing the occurrence of illegal logging practices through the powers given to the provincial government as well as the County Government, including efforts to: (a) monitoring and control the administering forest products derived from forest rights and (b) monitoring and control the administering forest products on the timber industry.